Multiple osteolytic primary peripheral T-cell bone lymphoma: the first case report. Issue 10 (October 2021) - Li, Chen; Wang, Weiguo; Xu, Lingyun; Zheng, Dingyun; Zhang, Miao; Zhang, Qin; Wu, Xiaoqian; Yao, Yue; Huang, Wenyue; Li, Xue; Ying, Peipei; Wang, Xiuxiu; et al.
Peripheral T-cell lymphoma accounts for about 10% of all cases of non-Hodgkin's lymphoma. However, less than 5% of patients with non-Hodgkin's lymphoma present with hypercalcaemia as the initial symptom, and less than 1% present with primary bone lesions. We herein describe a 76-year-old Chinese man who was diagnosed with primary bone adult T-cell lymphoma with extensive osteolysis, including bone loss in the radius, as the initial manifestation. He had developed severe generalised bone pain and an inability to raise his arms. X-ray examination revealed osteolytic destruction of the forearm with loss of the radial diaphysis. The patient was diagnosed with peripheral T-cell lymphoma based on his immunohistochemical results. He began treatment with the CHOPE chemotherapy regimen, which resulted in significant improvement of his bone pain.